EFEKTIVITAS DAN KEPUASAN PENGGUNA JEMBATAN PENYEBERANGAN ORANG (JPO) DI PASAR INDUK KRAMAT JATI - Achmad Nadjam; Mohamad Ferdiansyah; Hendrik Jonathan Sitorus (Jurnal Poli-Teknologi, 2018)
ABSTRACTThis research aims to determine how high the level of effectiveness, how the level of service and how the satisfaction of Pedestrian Bridge (PB) users in the Market Kramat Jati. Observations were made by calculating the volume of crossers using and not using the PB as well as the volume of vehicles passing during the morning rush hour and afternoon peak hours both on weekdays and on holidays. This data is used as the basis for the analysis of the effectiveness and determination of the appropriate type of crossing facilities. The observation of the user time of PB with the sample of 29 people for each observation time. Data collection also used questionnaires to 53 PB user respondents containing questions relating to the physical components of PB and supporting data that became the basic variables of consideration for the use of PB. The effectiveness analysis result shows that the JPO is not effective at the service level including category A. Based on the user satisfaction analysis, 59% are satisfied and very satisfied using the PB with the age range of 21-30 years old, the high school education, the most self employed, the monthly income 1 -3 million, the frequency of work usage < 2x per day, from destination to shopping / market with the intention to work.Keywords: Effectiveness, Pedestrian Bridge, User Satisfaction, Level Of Service.ABSTRAKPenelitian ini bertujuan untuk mengetahui seberapa tinggi tingkat efektivitas, bagaimanakah tingkat pelayanannya serta bagaimanakah kepuasan pengguna Jembatan Penyeberangan Orang (JPO) di Pasar Induk Kramat Jati. Pengamatan dilakukan dengan menghitung volume penyeberang yang menggunakan dan tidak menggunakan JPO serta volume kendaraan yang melintas pada jam sibuk pagi dan jam sibuk sore baik hari kerja maupun hari libur. Data ini digunakan sebagai dasar analisis efektivitas dan penentuan jenis sarana penyeberangan yang tepat.Dilakukan pengamatan waktu tempuh pengguna JPO dengan sampel sebanyak 29 orang untuk masing-masing waktu pengamatan.Pengumpulan data juga menggunakan kuesioner kepada 53 orang responden pengguna JPO yang berisi pertanyaan berkaitan dengan komponen-komponen fisik JPO dan data pendukung yang menjadi variabel dasar pertimbangan untuk penggunaan JPO.Hasil analisis efektvititas menunjukan bahwa JPO tersebut tidak efektif namus tingkat pelayanan termasuk kategori A. Berdasarkan analisis kepuasan pengguna, sebanyak 59% puas dan sangat puas menggunakan JPO dengan klasifikasirentang usia 21-30 tahun, pendidikan mayoritas SMA, pekerjaan terbanyak wiraswasta, penghasilan perbulan 1-3 juta, frekuensi pekerjaan pemakaian < 2x perhari, asal tujuan ke pertokoan/pasar dengan maksud bekerja.Kata Kunci : Efektivitas, Jembatan Penyeberangan Orang, Kepuasan Pengguna, Tingkat Pelayanan.